Effect of strengthening supervisory training on principal competence - BASUKI, S.; PERDINANTO, P.; HAMID, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The principal has an essential role in the school’s performance and achievement. That is why his competences needs to be improved. One of the ways to do so is by educating and training him. The sample of the study is the whole education and training members consisting of 30 principals from the Hulu Sungai Tengah Regency. The result of this study shows that there is a significant competences improvement after education and training was done. Based on the result, it can be stated that the strengthening of principal education and training is effective to increase their competences.RESUMEN El director tiene un papel esencial en el rendimiento de la escuela y es por eso que es necesario mejorar sus competencias. Una de las formas de hacerlo es educandolo y entrenandolo. La muestra del estudio es la totalidad de los miembros de educación y capacitación que consta de 30 directores de la Regencia Hulu Sungai Tengah. El resultado de este estudio muestra que hay una mejora significativa de las competencias después de su educación y capacitación. Con base en el resultado, se puede afirmar que el fortalecimiento de la educación y capacitación de los directores es efectivo para aumentar sus competencias.